High-resolution genomic profiling of chronic lymphocytic leukemia reveals new recurrent genomic alterations - Edelmann, Jennifer; Zenz, Thorsten; Lichter, Peter (Blood, 2012)
To identify genomic alterations in chronic lymphocytic leukemia (CLL), we performed single-nucleotide polymorphism-array analysis using Affymetrix Version 6.0 on 353 samples from untreated patients entered in the CLL8 treatment trial. Based on paired-sample analysis (n = 144), a mean of 1.8 copy number alterations per patient were identified; approximately 60% of patients carried no copy number alterations other than those detected by fluorescence in situ hybridization analysis. Copy-neutral loss-of-heterozygosity was detected in 6% of CLL patients and was found most frequently on 13q, 17p, and 11q. Minimally deleted regions were refined on 13q14 (deleted in 61% of patients) to the DLEU1 and DLEU2 genes, on 11q22.3 (27% of patients) to ATM, on 2p16.1-2p15 (gained in 7% of patients) to a 1.9-Mb fragment containing 9 genes, and on 8q24.21 (5% of patients) to a segment 486 kb proximal to the MYC locus. 13q deletions exhibited proximal and distal breakpoint cluster regions. Among the most common novel lesions were deletions at 15q15.1 (4% of patients), with the smallest deletion (70.48 kb) found in the MGA locus. Sequence analysis of MGA in 59 samples revealed a truncating mutation in one CLL patient lacking a 15q deletion. MNT at 17p13.3, which in addition to MGA and MYC encodes for the network of MAX-interacting proteins, was also deleted recurrently.
Gesehen am 18.04.2019